How to Safeguard University Students Against HIV Transmission? Results of a Cross-Sectional Study in Southern Italy - Licata, Francesca; Angelillo, Silvia; Oliverio, Antonella; Di Gennaro, Gianfranco; Bianco, Aida (Frontiers in Medicine, 2022)
Introduction: Young people represent a growing share of the group living with HIV, and monitoring the sexual behaviors of this vulnerable age group is necessary to control and prevent the HIV/AIDS pandemic. The present study has been conducted to investigate the level of knowledge and attitudes towards HIV infection and sexual behaviors among a sample of undergraduate university students in Southern Italy. Methods: Data were collected through an anonymous online questionnaire from 1 July to 31 July 2020 and included questions on socio-demographic and sexual history characteristics, knowledge and attitudes towards HIV infection, sexual behaviors, and sources of information about HIV. The eligibility criteria for the study were: age between 18 and 30 years and registered as an undergraduate student at the university. Results: Among the 1318 students who completed the survey, 62.5% knew that HIV can be transmitted through blood, vaginal secretions and semen. The overall median knowledge score was 10, and the main determinants of knowledge were being younger and attending to medical or life science majors. Less than half of the students (45.7%) reported that they always wear a condom during any sexual activity. Predictors of consistent condom use were being younger, having a later sexual debut and a good knowledge score. Conclusions: The study findings showed a not completely satisfactory level of knowledge and unsafe sex practices among university students. These results reiterate the need to tailor HIV prevention strategies among young individuals. Such a change could dispel misconceptions about HIV transmission and prevention that affect risk-taking sexual behaviors. These strategies may ultimately contribute to lessing the effect of HIV/AIDS transmission in Italy.